PENGEMBANGAN MODUL YANG DIAWALI DENGAN PETA KONSEP BERGAMBAR PADA MATERI SISTEM PENCERNAAN PADA MANUSIA UNTUK KELAS VIII SMP - Nengsih, Welni Gusma (STKIP PGRI Sumbar, 2014)
Module is the smallest unit learning program that systematically arranged, it can used by students independently without guidance of a teacher. The purpose of this study is to produce a module with concept map. The types concept map is picture concept map. The subject of this research is Human Disgetion System for class VIII SMP. This was a development research with a prodecural model. Models and procedure of development was develop with 4-D model, but for something reason this research just done on develop phase. Phases are define, design and develop. This research has been implemented and tested on January 13, 2014 by three teachers and 20 students of class VIII SMPN 4 Lengayang. The results of this study is module with picture concept map on the subject of Human Disgetion System average validity of modules was 87,59 % and very practicality of modul was 90,26 %. Based on the results, this research can be concluded that the development of modules based with picture concept map of material in human disgetion system development subject is valid and practical.